Chiral Salen-Based Organic Salts: Synthesis and Potential Antibacterial Activity - Marcin Gano; Michał Wójcicki; Ewa Janus (Molecules)
New chiral salen-based organic salts were synthesised and evaluated for their antibacterial activity against Serratia fonticola, Escherichia coli, and Enterobacter cloacae. Their structures and physicochemical properties, namely their specific rotation, melting point, thermal stability, and antibacterial efficacy, including minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), were determined. The synergy between chiral organic salts and bacteriophages was also demonstrated. [(RR)Sal.5C1.PhIM][Cl], [(RR)Sal.5C1.PhIM][BF4], and [(RR)Sal.5C1.Pyr][OTf] had the lowest MIC values (from 500 mg mL−1 for S. fonticola strain KKP 3685 to 2000 mg mL−1 for E. cloacae strain KKP 3692), while the highest MICs (>4000 mg mL−1) were observed for [(RR)Sal.5C1.Pyr][OTf] and [(RR)Sal.5C1.PhIM][NTf2] against E. cloacae strain KKP 3692. The impact of the tested compounds on phage activity was strain-specific. A synergistic effect of [(RR)Sal.5C1.PhIM][BF4] at 0.5 mg mL−1 in microcultures with Escherichia phage KKP 3710 (at MOI of 10 and 100) on the complete inhibition of the growth of E. coli strain KKP 3688 was observed. The combination of [(RR)Sal.5C1.PhIM])][OTf] at 1 mg mL−1 with the addition of phages (at each MOI) and at 0.5 mg mL−1 and MOI = 100 completely inhibited the growth of E. coli strain KKP 3688. Moreover, [(RR)Sal.5C1.PhIM])][OTf] at 1 mg mL−1 and 0.5 mg mL−1, when combined with Enterobacter phage KKP 3716, inhibited the growth of E. cloacae strain KKP 3692 slightly more effectively than the compound alone at the same concentrations. These results suggest that combining our antibacterial agents can reduce chemical compound concentrations, with effects depending on the bacteria.